Ion Exchange Behaviour of Tin (IV) Molybdophosphate Towards Alkaline Earth Metal Ions - Pal Gupta, Anek; Nasir Abbas Rizvi, S.; Varshney, P.K. (Asian Journal of Chemistry, 2010)
Samples of tin (IV) molybdophosphate were synthesized by mixing the solutions of tin (IV) chloride and molybdophosphoric acid. A sample which exhibits ion exchange capacity for Na+ 0.85 Meq/g was selected for the studies. The ion exchange equilibria of Mg2+, Ca2+, Sr2+ and Ba2+ with hydrogen form of tin (IV) molybdophosphate have been studied. The values for KHm, ΔGº, ΔHº, ΔSº and ΔSex have been determined for the equilibria at 30º, 45º and 60ºC.